2004
DOI: 10.1007/s11882-004-0047-8
|View full text |Cite
|
Sign up to set email alerts
|

Chemokines in eosinophil-associated gastrointestinal disorders

Abstract: Eosinophil-associated gastrointestinal disorders (EGDs) are characterized by a pronounced cellular inflammation. Recent clinical and experimental investigations have implicated a family of molecules known as chemokines in the regulation of leukocyte recruitment in these diseases. The underlying cellular and molecular mechanisms involved in chemokine-mediated cellular infiltration are largely unknown. In this review, we describe the role of CD4+ T cells and eosinophils in the clinical manifestations of EGDs and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 55 publications
0
30
0
Order By: Relevance
“…1). 38,49 The gastrointestinal tract is the main nonhematopoietic organ where eosinophils reside in the healthy state. Eosinophils are normally present in the lamina propria, but the number of eosinophils regarded as pathological for various sites along the gastrointestinal tract is debated; the highest concentrations are found in the cecum and appendix.…”
Section: The Eosinophilmentioning
confidence: 99%
“…1). 38,49 The gastrointestinal tract is the main nonhematopoietic organ where eosinophils reside in the healthy state. Eosinophils are normally present in the lamina propria, but the number of eosinophils regarded as pathological for various sites along the gastrointestinal tract is debated; the highest concentrations are found in the cecum and appendix.…”
Section: The Eosinophilmentioning
confidence: 99%
“…selectins and integrins) and integrin receptors (e.g. vascular cell adhesion molecule-1 [VCAM-1], mucosal addressin cell adhesion molecule-1 [MAdCAM-1] and intercellular adhesion molecule-1 [ICAM-1]) expressed on vascular endothelial cells [120, 121]. For example, eosinophil recruitment to the site of allergic inflammation in the lung and skin is regulated by VLA-4 (α 4 β 1 -integrin)/VCAM-1-dependent processes [122,123,124,125,126].…”
Section: Eosinophilic Gastrointestinal Diseases (Egid)mentioning
confidence: 99%
“…Our studies demonstrating a critical role of MAdCAM-1/α 4 β 7 -integrin-dependent pathway in eosinophil recruitment into the small intestine and ICAM-1/MAC-1 and LFA-1-pathways for recruitment into the large intestine suggest that differential adhesion systems regulate eosinophil recruitment into discrete GI compartments. Paradoxically, we have demonstrated that the recruitment of eosinophils into these various GI compartments (small and large intestine) is primarily regulated by eotaxin-1 [121]. How eotaxin-1 selectively recruits eosinophils into discrete GI compartments in the absence of other GI segment involvement remains to be determined.…”
Section: Eosinophilic Gastrointestinal Diseases (Egid)mentioning
confidence: 99%
“…To elucidate the etiology of disease, we developed an experimental model oral antigen-induced eosinophilic GI inflammation that mimics EGE [39]. Oral administration of the antigen ovalbumin to OVA-sensitized mice induced a pronounced eosinophilic inflammation of the small intestine (duodenum, jejunum, and ileum).…”
Section: Experimental Eosinophilic Gastroenteritismentioning
confidence: 99%
“…Notably, eosinophils in the jejenum of oral antigen-challenged mice were in close proximity to damaged enteric nerves [39]. The enteric nerves contained swollen, enlarged axonal chambers with variable loss of internal organelles, including the dense core granules of Schwann cells.…”
Section: Experimental Eosinophilic Gastroenteritismentioning
confidence: 99%